Supraglottic airway devices in neuroanesthesia practice: A narrative review - Balaji Vaithialingam; Varadarajan Bhadrinarayan; Satish Rudrappa (Journal of Anaesthesiology Clinical Pharmacology)
Supraglottic airway devices (SADs) have a great application as an alternative to tracheal intubation, prompting a paradigm shift in routine anesthetic practice. However, its usage in neuroanesthesia is limited and debatable, considering the clinical challenges and complexity of neurosurgical procedures. Even though literature evidence exits regarding successful airway management with SADs in neurosurgery, there is no clear-cut evidence or consensus among anesthesiologists. Articles were searched in PubMed and Google Scholar by using the keywords “Supraglottic airway” AND “Laryngeal Mask” OR “LMA” AND “Craniotomy” over the past 30 years. In addition, a manual search was performed (with additional keywords “neurosurgery,” spine surgery,” “I-gel,” “ILMA,” “awake craniotomy,” “radiology,” “electroconvulsive therapy,” and “magnetic resonance imaging”) to retrieve additional articles. The primary goal of this narrative review is to determine the applicability of SADs in various neurosurgical settings. According to the review, SADs play an important role as a rescue device during intraoperative emergencies such as accidental tracheal extubation (supine, lateral, and prone positions with head fixed on cranial pins), sudden airway loss due to seizure during awake craniotomy, postoperative airway loss following trans-nasal pituitary surgeries, and macroglossia. SADs can be used successfully for short-duration minimally invasive elective procedures such as cranioplasty, burr hole evacuation of subdural collection, battery implantation for deep brain stimulation, vario-guided biopsies, and minimally invasive spine surgeries. Furthermore, SADs serve a significant function in blunting extubation responses, thereby preventing cerebral edema and tumor bed hemorrhage. Only a few studies have supported the use of SADs in long-duration major intracranial tumour surgeries, making its use controversial in major surgeries where intracranial pressure control is the key. The SADs also have clinical utility in various non-operating room neuroanesthesia procedures.